Pengaruh Kompensasi Terhadap Kinerja Aparatur Pemerintahan Kampung onggari Distrik Malind di Kabupaten Merauke - Semuel Batlajery; Marlyn Eleida Alfons (EKONOMI & SOSIAL, 2014)
The study aims to identify and analyze the Compensation Effect on Performance of Government Apparatus Village Onggari Malind District district. Merauke.       The research method in this study is a case study approach, this type of research is descriptive quantitative, and the nature of the research is the explanation (explanatory). Method of data collection through interviews and questionnaires. Analysis of the data used is a simple linear regression. The population of the village is Onggari Apparatus Malind District Merauke district, amounting to 30 respondents. Determination of the number of samples in this study uses total sampling so that the number of samples taken as many as 30 people.       The results of the data analysis was conducted on all data obtained, it can be concluded that the compensation effect on performance. This is evidenced by the value of t is greater than t table value is 4.588> 1.943 with a significant level of 0.01 <0.05. showed that 42.9% Compensation variables affect the performance. while as many as 57.1% is explained by other variables not examined in this study.